2022
DOI: 10.3390/nu14030434
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Dietary Outcomes of Celebrities and Influencers in Marketing Unhealthy Foods to Children: A Systematic Review and Meta-Analysis

Abstract: Celebrities, including influencers, are commonly used to market products that are high in fat, sugar, and salt (HFSS) to children but the impact on dietary outcomes has been unclear. The primary aim of this study was to systematically review the literature and quantify the impact of celebrities in HFSS marketing on children’s dietary outcomes. We searched eight databases and included studies from all countries and languages published from 2009 until August 2021. Participants were defined as under 16 years, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Social media also contributes to the promotion of food products to users ( 54 ). Influencers, youtubers show specific food products, recommend their purchase, and they are not always healthy ( 55 ). These are sponsored advertisements paid for by large food concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Social media also contributes to the promotion of food products to users ( 54 ). Influencers, youtubers show specific food products, recommend their purchase, and they are not always healthy ( 55 ). These are sponsored advertisements paid for by large food concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in childhood often continues into adulthood ( Singh et al, 2008 ), and increased body weight is related to chronic disease including type 2 diabetes, cardiovascular disease, and hypertension ( National Institutes of Health, 1998 ; Dietz, 2004 ; Daniels et al, 2005 ; Freedman et al, 2007 ). Many studies have indicated that food marketing plays a critical role in promoting the current obesity epidemic particularly in amplifying the obesogenic environment that younger children in the United States find themselves in Harris et al (2009) , Zimmerman (2011) , Ustjanauskas et al (2013) , Harris and Kalnova (2018) , Coates et al (2019) , Bragg et al (2021) , and Packer et al (2022) .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the nutrition labelling-related fields, bibliometric analysis, especially co-citation analysis, has not been widely used. Crocker et al [44] reviewed and meta-analysed the literature on FoPL based on 2 years of research. Talati et al [45] systematically reviewed the literature to assess the consumers' responses to health claims on FoPL [46].…”
Section: Bibliometric Analysis and Centrality Measuresmentioning
confidence: 99%